PPM PEMBERDAYAAN PENJAHIT LANSIA MENUJU HIDUP SEHAT & PRODUKTIF DI KELURAHAN DUKUH PAKIS SURABAYA - Nurjannah Nurjannah; Dwi Lesno P; Bayu Murti (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
Abstract The main health problem in the elderly is cardiovascular disease. This can be because the individual's lifestyle ignores its negative effects on health and even doesn't know what exercise is. The purpose of community service is to determine the increase in citizens' knowledge about increasing knowledge, attitudes and skills in improving and maintaining the health status of the elderly, improving heart health for the elderly, reducing the risk of heart disease. Elderly Tailor MSMEs can be very productive in their activities, therefore a healthy life is needed so that they can be productive in producing work. Therefore, hypertension management education is very necessary that can help the elderly to monitor health developments so that they can continue to carry out sewing activities. The Service Team also provides mentoring facilities entrepreneurship about sewing patterns correctly and marketing products with social media, in order to produce good production and this sewing business can be sustainable. Keywords: Hypertension Management; elderly; Productive